Anaplastic Thyroid Cancer in Sicily: The Role of Environmental Characteristics - Tavarelli, Martina; Malandrino, Pasqualino; Vigneri, Paolo; Richiusa, Pierina; Maniglia, Adele; Violi, Maria A.; Sapuppo, Giulia; Vella, Veronica; Dardanoni, Gabriella; Vigneri, Riccardo; Pellegriti, Gabriella (Frontiers in Endocrinology, 2017)
Background: Anaplastic thyroid cancer (ATC) is a rare but extremely aggressive cancer of the thyroid, contributing up to 30-40% of thyroid cancer-specific mortality. We analyzed ATC characteristics and survival rates in Sicily to evaluate the possible influence of environmental factors. With this aim data regarding ATC incidences in urban/rural and industrial, iodine deficient and volcanic vs. control areas were compared in Sicily as well as ATC data from Sicily and USA. Methods: Using the Sicilian Register of Thyroid Cancer (SRTC) database incidence, age, gender, tumor size and histotype, extrathyroidal extension, stage and coexistence with pre-existing differentiated thyroid cancer (DTC) were evaluated in different areas of Sicily and also compared with Surveillance Epidemiology and End Results (SEER) data in USA. Results: Fortythree ATCs were identified in Sicily in the period 2002-2009. In our series only age < 70 years at diagnosis (p=0.01), coexistence with DTC (p=0.027) and tumor size ≤6 cm (p=0.012) were significant factors for increased survival at univariate analysis (only age at multivariate analysis). No difference in ATC incidence was found in urban vs rural areas and in iodine-deficient and industrial vs. control areas. In contrast, in the volcanic area of Sicily, where DTC incidence is doubled relative to the rest of the island, also ATC incidence was increased. ATC data in Sicily were similar to those reported in the same period in the USA where overall survival rate at 6 and 12 months, however, was smaller. Conclusions: The similar ATC data observed in Sicily and USA (having different genetic background and lifestyle) and the increased ATC incidence in the volcanic area of Sicily paralleling the increased incidence of papillary thyroid cancer, are compatible with the possibility that casual additional mutations, more frequent in a background of increased cell replication like DCT, are the major causes of ATC rather than genetic background and/or direct environmental influences.